2001
DOI: 10.1152/jappl.2001.91.2.919
|View full text |Cite
|
Sign up to set email alerts
|

Chronic airway infection leads to angiogenesis in the pulmonary circulation

Abstract: In both pulmonary and systemic hypertension, the walls of the arteriolar vessels are thickened and the lumen size is reduced, leading to increased total vascular resistance. It has been reported previously that chronic airway infection and inflammation lead to increased wall thickness in the pulmonary vasculature, without the development of pulmonary hypertension. The aim of the present study was to examine quantitatively the remodeling of intra-acinar blood vessels in chronically infected rat lungs. Adult rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 20 publications
2
50
0
Order By: Relevance
“…The left lung was isolated and fixed for morphometric examination as previously described (25,26). The extent of histologic lung damage was determined using quantitative stereological techniques by blinded assessors as previously described (27).…”
Section: In Vivo Experimental Ventilation-induced Alimentioning
confidence: 99%
“…The left lung was isolated and fixed for morphometric examination as previously described (25,26). The extent of histologic lung damage was determined using quantitative stereological techniques by blinded assessors as previously described (27).…”
Section: In Vivo Experimental Ventilation-induced Alimentioning
confidence: 99%
“…The point counting grid was used for volume density analysis. The relative wall thickness of each artery (VWT) was calculated by the formula: VWT5(Ro-Ri)/Ro [30]. Three sections of each mouse lung from five to six animals per group were analysed.…”
Section: Vessel Wall Thickness Measurementmentioning
confidence: 99%
“…In adult dogs after pneumonectomy there is growth of new alveolar septa and alveolar capillaries in the residual left lung. 23 Schraufnagel et al have reported evidence of pulmonary angiogenesis in the rat lung after induction of biliary cirrhosis. 24 Schraufnagel has also suggested there is new vessel formation in the lungs of a patient with pulmonary venoocclusive disease.…”
mentioning
confidence: 99%